2021
DOI: 10.1002/jmv.27093
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide screening of SARS‐CoV‐2 infection‐related genes based on the blood leukocytes sequencing data set of patients with COVID‐19

Abstract: Coronavirus disease 2019 (COVID‐19) is a global epidemic disease caused by a novel virus, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), causing serious adverse effects on human health. In this study, we obtained a blood leukocytes sequencing data set of COVID‐19 patients from the GEO database and obtained differentially expressed genes (DEGs). We further analyzed these DEGs by protein–protein interaction analysis and Gene Ontology enrichment analysis and identified the DEGs closely related to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
4
16
1
Order By: Relevance
“…5B). We observed a substantial overlap in DEGs/DAGs in wbRN cfRNA when comparing MIS-C to controls (n=494) and COVID- 19 [34][35][36][37][38] . Similar to the gene abundance profiles, differential pathway analysis revealed minimal overlap in top enriched pathways between wbRNA and cfRNA for each subgroup comparison (Supplemental Fig.…”
Section: Comparative Analysis Of Plasma Cell-free Rna and Whole Blood...mentioning
confidence: 90%
See 1 more Smart Citation
“…5B). We observed a substantial overlap in DEGs/DAGs in wbRN cfRNA when comparing MIS-C to controls (n=494) and COVID- 19 [34][35][36][37][38] . Similar to the gene abundance profiles, differential pathway analysis revealed minimal overlap in top enriched pathways between wbRNA and cfRNA for each subgroup comparison (Supplemental Fig.…”
Section: Comparative Analysis Of Plasma Cell-free Rna and Whole Blood...mentioning
confidence: 90%
“…C to moderate-to-severe COVID-19 (n=9). Of the 9 DEGs/DAGs that overlap when comparing MIS-C to moderate-to-severe COVID-19, seven had been previously reported in association with COVID-19 (IFI6, IFI44L, RSAD2, LY6E, EPSTI1, XAF1, MX1)[34][35][36][37][38] . Similar to the gene abundance profiles, differential pathway analysis revealed minimal overlap in top enriched pathways between wbRNA and cfRNA for each subgroup comparison (Supplemental Fig.5C and D).…”
mentioning
confidence: 99%
“…Therefore, early intervention to prevent overexpression of CCL5 can restore immune balance in COVID-19 patients and prevent disease progression ( 311 , 314 ). Moreover, 2′–5′‐oligoadenylate synthetase‐like ( OASL ), the other hub-high traffic gene of midnightblue module, is an interferon-stimulating gene with a key role in antiviral defense mechanisms ( 326 ) and with potential as a diagnostic biomarker for COVID-19 ( 327 ).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal 24 feature genes, which were further analyzed by consulting the retrieved literature, we found that four genes (XAF1, OAS2, CES1, RPS8) have been reported in COVID-19. Gao et al ( 23 ) found that XAF1 was abnormally strongly expressed in COVID-19 patients and positively correlated with the expression of ARS-CoV-2 invasion-related genes (ACE2, TMPRSS2, CTSB, and CTSL). In contrast, XAF1 was found to be associated with SARS infection by Park and Harris ( 24 ).…”
Section: Discussionmentioning
confidence: 99%